2020
DOI: 10.3390/pharmaceutics12030197
|View full text |Cite
|
Sign up to set email alerts
|

Spray-Dried Amorphous Solid Dispersions of Griseofulvin in HPC/Soluplus/SDS: Elucidating the Multifaceted Impact of SDS as a Minor Component

Abstract: This study aimed to elucidate the impact of a common anionic surfactant, sodium dodecyl sulfate (SDS), along with hydroxypropyl cellulose (HPC) and Soluplus (Sol) on the release of griseofulvin (GF), a poorly soluble drug, from amorphous solid dispersions (ASDs). Solutions of 2.5% GF and 2.5%–12.5% HPC/Sol with 0.125% SDS/without SDS were prepared in acetone–water and spray-dried. The solid-state characterization of the ASDs suggests that GF–Sol had better miscibility and stronger interactions than GF–HPC and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…Figure S3 (Supplementary Materials) shows that XRPD diffractograms revealed that both non-processed HPC and processed HPC exhibited two peaks at about 8° and 20°, indicating that this polymer has an amorphous domain. This aligns with data by Rahman et al [ 37 ] that confirmed the same peaks for non-processed HPC. Differing HPC concentrations depicted the same peaks, although their intensity was shown to be slightly lower for the SASD HPC.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Figure S3 (Supplementary Materials) shows that XRPD diffractograms revealed that both non-processed HPC and processed HPC exhibited two peaks at about 8° and 20°, indicating that this polymer has an amorphous domain. This aligns with data by Rahman et al [ 37 ] that confirmed the same peaks for non-processed HPC. Differing HPC concentrations depicted the same peaks, although their intensity was shown to be slightly lower for the SASD HPC.…”
Section: Resultssupporting
confidence: 92%
“…In addition, the literature has also reported a few small crystalline peaks between 29–47° [ 38 ]. Rahman et al [ 37 ] uncovered a small endothermic peak around 190–200 °C for the DSC thermogram of raw HPC. This probably results from the fusion of the small crystalline fraction of largely amorphous HPC or a liquid crystal isotropic transition [ 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Greenhalgh et al and Hancock et al have suggested that the system can be considered miscible if the difference between the solubility parameter value of components is less than 7 MPa 1/2 , while the difference greater than 10 MPa 1/2 should be considered as a sign of immiscibility. , Schilling et al have used these criteria to conclude miscibility between diltiazem hydrochloride and citric acid . Sathigari et al and Prasad et al have used these criteria to demonstrate the miscibility of eudragit EPO with efavirenz and indomethacin, respectively. , Apart from this, numerous reports have discussed the difference in the solubility parameter as an indicator of drug-polymer miscibility. …”
Section: Methods For the Evaluation Of Drug-polymer Solubility And Mi...mentioning
confidence: 99%
“…These are among the simplest dosage forms, and may contain the drug and polymer in a binary solid-dispersion system while additionally containing surfactant in a tertiary system. Solid dispersions can be fabricated by using different methods, such as solvent evaporation [ 6 ], melting method [ 10 ], spray drying [ 11 ], hot melt extrusion, supercritical fluid technology [ 12 ] and electrostatic spinning [ 13 ]. However, one of the most promising and cheap methods is solvent evaporation, which involves digestion of the drug and carrier in single or multiple solvents to make a clear solution, followed by solvent evaporation [ 5 , 14 ].…”
Section: Introductionmentioning
confidence: 99%